Evaluating time to maximum rate (TMR) and self-accelerating decomposition temperature (SADT) of self-polymerizing vinyl acetate monomer. (July 2021) - Cheng, Yu-Chi; Huang, Yun-Shan; Wang, Yih-Wen
Abstract: Vinyl acetate monomer (VAM) is widely used as a chemical intermediate producing a variety of copolymer products. Besides, VAM has the tendency to readily decompose into free radicals and ions that initiates the self-sustaining polymerization reaction. The non-isothermal experiments of VAM were performed using differential scanning calorimetry (DSC), and the calculations of the kinetic parameters from temperature-programmed DSC curves have been evaluated by the isoconversional method. The thermal analysis of VAM was proceeded using the advanced thermal analysis software (AKTS) to figure out the time to maximum rate (TMR) and self-accelerating decomposition temperature (SADT) for a proactive safety design of VAM. Subsequently, the kinetic model is used to predict the potential thermal runaway in the VAM-PVAc polymerizing process. Highlights: VAM is considered flammable and reactive when improperly handled. VAM is liable to undergo an exothermic reaction resulting from its self-sustaining polymerization reaction. AKTS can be used to facilitate kinetic analysis of DSC data for determining TMR and SADT of VAM.